Analysis of Purity and Concentration of DNA Isolated in Dragonfly (Onychogomphus forcipatus) - Alfi Sophian; La Ode Nasir (Program of Biology Education, Universitas Lambung Mangkurat, 2022)
Analysis of the purity and concentration of DNA isolation results was carried out using samples of dragonflies (Onychogomphus forcipatus) species of insects. This research is important because there are many kinds of research in the molecular field that require good DNA isolation techniques to support the success of the research. The purpose of this paper is to provide information about the quality of the isolated DNA seen using the purity and concentration parameters. The extraction method uses the centrifuge column method. The isolated data were analyzed statistically using the average test. The results of DNA isolation showed that the average concentration value was in the range of 60.10 – 69.95. The analysis of the purity of the isolated DNA read at the A260/A280 ratio was in the range of 1.817 – 1.929, while the purity analysis at the A260/A230 ratio was in the range of 0.760 – 0.822. Based on the results of the study, it can be concluded that the analysis of the purity and concentration of DNA from the isolation of dragonfly samples was in a good category at the A260/A280 ratio, while the purity read at the A260/A230 ratio was below the value categorized as good.